HUBUNGAN UMUR DAN PENGETAHUAN DENGAN KEPUTUSAN IBU DALAM PEMILIHAN TENAGA PENOLONG PERSALINAN DI WILAYAH KERJA PUSKESMAS GUNUNG SAHILAN TAHUN 2017 - Rizki Rahmawati Lestari (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2017)
Aid deliveries by skilled health personnel is one of the strategies in dealing with mother and child health issues. Based on the results of data Basic Health Research (RISKESDAS) in 2015 showed that the coverage of deliveries by skilled health personnel reached 84.78%, coverage in PHC Gunung Sahilan delivery assistance by health workers 77.21% in 2016, while the national target coverage of deliveries by skilled health personnel for 90%. This study aims to determine the relationship of age and knowledge with the selection decision birth attendants. Survey research design was cross sectional analytic approach. The population in this study were mothers who had infants aged 0-6 months in the Work Area Health Center Gunung Sahilan period in June 2017. Proportional sampling technique is random sampling as many as 133 people. The research was conducted on July 15 to 25, 2017, with a research instrument in the form of questionnaires. Data analysis is univariate and bivariate, using Chi-square test. The results found that age and knowledge related to the selection decision birth attendants with p value of each variable are 0.000 and 0.000.